2010
DOI: 10.1142/s021797921005507x
|View full text |Cite
|
Sign up to set email alerts
|

Excitations Near the Boundary Between a Metal and a Mott Insulator

Abstract: A heterostructure of a semi-infinite metal and a Mott insulator is considered. It is supposed that both materials have an identical lattice spacing and hopping integrals and differ in the Hubbard repulsion, which is negligible in the metal and exceeds the critical value for the Mott transition in the insulator. At half-filling and for low temperatures, the insulator has the long-range antiferromagnetic order. Its low-lying elementary excitations are standing spin waves and a spin-wave mode which is localized n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
4
6
0
Order By: Relevance
“…The results of Figs. 2 and 3 are rather different from previous work of Sherman et al 25 who found that the antiferromagnetic order can penetrate into the metal to a depth of ten lattice spacings, but are consistent with the shorter-range effects described in Refs. 11 and 12.…”
Section: Magnetic Propertiessupporting
confidence: 60%
“…The results of Figs. 2 and 3 are rather different from previous work of Sherman et al 25 who found that the antiferromagnetic order can penetrate into the metal to a depth of ten lattice spacings, but are consistent with the shorter-range effects described in Refs. 11 and 12.…”
Section: Magnetic Propertiessupporting
confidence: 60%
“…The dominant feature of the coupling of the metal and strongly interacting material is a suppression of magnetic order on the correlated side. We did not observe the converse phenomenon, namely a significant penetration of magnetism into the metal, as has been noted in [10]. It is possible this difference arises from the lower value of the on-site interaction, U/t = 4, used here, compared to U/t ≈ 17 in [10].…”
supporting
confidence: 47%
“…We did not observe the converse phenomenon, namely a significant penetration of magnetism into the metal, as has been noted in [10]. It is possible this difference arises from the lower value of the on-site interaction, U/t = 4, used here, compared to U/t ≈ 17 in [10]. Such large couplings are difficult to treat in DQMC.…”
supporting
confidence: 41%
“…For J 3 = 0 the problem reduces to two noninteracting semi-infinite antiferromagnets, which spin excitations were considered in Refs. [7,[9][10][11]. As mentioned in the Introduction, the spectrum of each antiferromagnet consists of a quasi-2D mode of spin waves, which are mainly located in two nearboundary layers, and bulk modes of standing spin waves in the rest of the crystal.…”
Section: Spin Excitationsmentioning
confidence: 99%
“…Spin excitations and correlations near this interface were investigated in Refs. [6][7][8][9][10][11]. In particular, it was shown that the antiferromagnet is divided into two regions with different spin excitations [9][10][11].…”
Section: Introductionmentioning
confidence: 99%